A spatial analysis of gating in Bloemfontein, South Africa - Ferreira Verno; Visser Gustav (Bulletin of Geography. Socio-Economic Series)
Growing trends of fear and insecurity in cities have sparked the re-visitation of gating, posing significant problems for citizens and policy makers alike. Gated developments are a global phenomenon occurring in diverse countries in both the developed North and developing South. Metropolitan areas in South Africa have also witnessed a rapid increase in the number and spread of gated developments since the late 1980s. Development of enclosed neighbourhoods has become increasingly popular, gaining widespread support for their utopic lifestyle and safety features. On the whole, high levels of crime and fear of crime have led to the construction of defensible space, in the form of gated developments, resulting in elevated levels of segregation. This paper provides a spatial analysis on gated developments in the non-metropolitan setting of Bloemfontein. The pattern and timeframe of gating in this city is shown to be similar to those found elsewhere in South Africa and, indeed, globally. Overall, it is the contention that gating is a trend not only seen in large metropolitan areas, but across the entire urban hierarchy of South Africa, and, as a consequence, requires investigation far beyond its metropolitan regions to more fully understand gated developments.